Language Barrier, Academic Stress and Cultural Differences Towards International Students’ Satisfaction - Talish Alam,; Mohd Asmadi Mohd Angsor, (Research in Management of Technology and Business, 2024)
International students pursuing higher education encounter a slew of obstacles, including linguistic stumbling blocks, academic stress, and cultural barriers. The fundamental goal of the research is to investigate the link between these difficulties, specifically, language hurdles, academic stress, and cultural differences and their influence on student happiness. The research intends to give significant insights into the complex dynamics that impact the overall happiness of international students in the educational landscape by diving into these linked elements. Furthermore, this research utilizes quantitative approaches by means of survey distribution to the participants. Respondents for this study are international students to whom the questionnaires are distributed. In accordance with the sample size formula furnished by Krejcie & Morgan, a suitable number of 285 participants is considered for incorporation into this research endeavor. The research, which combines descriptive and correlational methods, finds a strong connection between several variables and the level of satisfaction felt by students. Researchers need to know more about the challenges that international students encounter, and this study helps fill that gap. Finding ways to make students satisfied is the driving force behind this research.